Coating composition and film manufactured therefrom
A coating composition with silsesquioxane resins improves moisture resistance and surface hardness of triethylcellulose films, addressing durability issues while maintaining optical properties.
Patent Information
- Application Number
- JP2024178514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-12-30
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-28
AI Technical Summary
Triethylcellulose films exhibit high water permeability and low surface hardness, leading to reduced durability in humid environments and scratches, which is a challenge for polarized boards requiring moisture permeability and improved adhesion.
A coating composition containing a blend of cage-type and ladder-type silsesquioxane resins, along with optional additives, is applied to enhance moisture resistance and surface hardness without compromising optical properties.
The coating composition significantly reduces water permeability and enhances surface hardness, resulting in durable triethylcellulose films suitable for polarized boards.
Smart Images

Figure 2025013840000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating composition, and more particularly to a coating composition that can improve moisture resistance and surface hardness of a triacetyl cellulose film by a simple coating process using the coating composition on the triacetyl cellulose film without impairing the optical properties of the triacetyl cellulose film. [Background technology]
[0002] The following description merely provides background information related to the present invention and is not intended to constitute prior art.
[0003] Triacetyl cellulose film is a natural plastic film that has been used for photographic film for more than half a century. It has a unique amorphous structure, which allows it to exhibit unique mechanical and optical properties. In particular, it has a very low level of birefringence and excellent optical isotropy. Based on these properties, triacetyl cellulose film is widely used for optical films such as protective films for polarizing plates and supports for viewing angle widening films. In particular, triacetyl cellulose film used for protective films for polarizing plates has high purity, good transparency and optical isotropy, no phase difference, and adheres to both sides of polyvinyl alcohol film to improve strength and protect polyvinyl alcohol substrate from heat and humidity. In addition, since a water-soluble adhesive is used to adhere the polyvinyl alcohol substrate to the triacetyl cellulose film, the triacetyl cellulose film used therefor is required to have an appropriate moisture permeability so that moisture can escape after adhesion. However, looking at the recent trend in polarizing plate manufacturing, the adhesive used in the past has been rapidly changed to a reactive adhesive, and the process is also changing so that the moisture permeability of triacetyl cellulose film is no longer required.
[0004] In addition, triacetyl cellulose films have a higher moisture permeability than other films, and their durability is easily reduced in high temperature and humid environments, leading to defects in polarizers. The hardness of the surface, which is vulnerable to scratches, has also been pointed out as an ultimate issue that must be resolved.
[0005] In order to overcome the above problems, many attempts have been made in the industry. For example, in Korean Patent Publication No. 10-2016-0080656, a coating layer containing a siloxane oligomer was formed on a triacetyl cellulose film to overcome the moisture permeability and surface hardness of the triacetyl cellulose film. However, the surface hardness of the above technology was limited to 3H, and the high moisture permeability caused by the film still resulted in problems of reduced durability. Summary of the Invention [Problem to be solved by the invention]
[0006] In order to solve the above problems of the prior art, the present invention aims to provide a coating composition that can significantly improve moisture resistance and surface hardness without impairing the optical properties of the film through a simple coating process.
[0007] Another object of the present invention is to provide a film having improved moisture permeability and surface hardness using the coating composition, and an optical film including the same. [Means for solving the problem]
[0008] In order to achieve the above object, the present invention provides The present invention provides a coating composition containing a silsesquioxane oligomer in which the weight ratio of a cage-type silsesquioxane resin to a ladder-type silsesquioxane resin is 10% by weight:90% by weight to 80% by weight:20% by weight.
[0009] The present invention also provides a film obtained by coating the coating composition on a substrate and curing it. Effect of the Invention
[0010] The coating composition according to the present invention can improve moisture resistance and surface hardness without impairing the excellent optical properties of the film through a simple coating process. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 illustrates a coated film according to one embodiment of the present invention, where the coating layer is shown to be thicker than it actually is. [Diagram 2] FIG. 2 is a diagram showing the bonding structure of a hard-coated triacetyl cellulose film according to one embodiment of the present invention. [Diagram 3] 1 is a SEM photograph of a cross section of a coated triacetyl cellulose film according to Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;
[0013] Throughout the specification, when a part is said to "comprise" a certain element, this means that it can further include other elements, but not to the exclusion of other elements, unless specifically stated to the contrary.
[0014] The coating composition of the present invention contains a silsesquioxane oligomer in which the weight ratio of the cage-type silsesquioxane resin to the ladder-type silsesquioxane resin is 10% by weight:90% by weight to 80% by weight:20% by weight.
[0015] Specifically, the coating composition of the present invention can include the silsesquioxane oligomer; an initiator; and a solvent.
[0016] The silsesquioxane oligomer may have both a cage structure and a ladder structure, and specifically, may be a ladder-type silsesquioxane resin represented by Chemical Formula 1 to which a cage-type silsesquioxane resin represented by Chemical Formula 2 is bonded. [ka] In the above Chemical Formula 1, R1, R2, R3, and R4 each independently represent a methyl group, which may be substituted or unsubstituted; a phenyl group; an amino group; a (meth)acrylic group; a vinyl group; an epoxy group; a thiol group; or an ultraviolet absorber; and n represents an integer of 1 to 100. R5, R6, R7, and R8 are each independently hydrogen; a C1-C10 alkyl group substituted or unsubstituted; or a linking group represented by the following chemical formula 2, and at least one of R5, R6, R7, and R8 is linked to the following chemical formula 2: [ka] In the above Chemical Formula 2, R is independently a methyl group, a phenyl group, an amino group, a (meth)acrylic group, a vinyl group, an epoxy group, a thiol group, or an ultraviolet absorber, each of which is substituted or unsubstituted with a substituent; R is independently a hydrogen atom or a C1-C 10 is an alkyl group of the formula n is an integer from 3 to 6; In the above Chemical Formula 1 or 2, the substituents are each independently deuterium, a halogen, an amine group, an epoxy group, a (meth)acrylic group, a thiol group, an isocyanate group, a nitrile group, a nitro group, or a phenyl group.
[0017] The ultraviolet absorber is a structure that absorbs ultraviolet rays having a wavelength range of 200 nm to 400 nm, and commonly used ultraviolet absorbers include benzophenone-based (ultraviolet absorption range: 300 to 380 nm), benzotriazole-based (absorption range: 300 to 385 nm), salicylic acid-based (absorption range: 260 to 340 nm), and acrylonitrile-based (absorption range: 290 to 400 nm).
[0018] The silsesquioxane oligomer used in the present invention has a cage structure ratio of 10 to 80% by weight in the oligomer, so that the moisture permeability of the TAC film is 100 g / m 2 Specifically, the silsesquioxane oligomer has a cage structure ratio of 20 to 50% by weight, so that the moisture permeability of the TAC film is 85 g / m or less. 2 More specifically, the silsesquioxane oligomer has a cage structure ratio of 25 to 35% by weight, so that the moisture permeability of the TAC film is 70 g / m 2 It can satisfy excellent moisture resistance of less than .day.
[0019] Specifically, when n is 4, the linking group represented by Chemical Formula 2 may have a structure as represented by Chemical Formula 3 below. [ka]
[0020] In the above Chemical Formula 3, * is a linking site, and R and R0 are as defined in Chemical Formula 2.
[0021] In the coating composition of the present invention, the content of the silsesquioxane oligomer is preferably 20 to 60% by weight. When it is within this range, the excellent moisture resistance and excellent surface hardness of the TAC film can be simultaneously satisfied.
[0022] Triacetyl cellulose films are prone to decrease in durability in humid environments due to their high moisture permeability, which is particularly a cause of defects in the polarizer of a polarizing plate using the film. In view of this, the present invention provides a triacetyl cellulose film with improved durability, by coating a composition containing silsesquioxane on the triacetyl cellulose film, thereby significantly reducing the moisture permeability of the triacetyl cellulose film and significantly improving the surface hardness.
[0023] Ladder-type silsesquioxane alone is highly brittle, and the coating film is easily cracked and broken during coating, making it difficult to form a coating film. In addition, cage-type silsesquioxane alone rearranges over time after coating, making it unable to maintain its initial performance, and there is a limit to reducing moisture permeability due to the voids in the cage structure itself.
[0024] Therefore, the present inventors have prepared a silsesquioxane having both a cage structure and a ladder structure in one molecule. In addition, the moisture permeability and surface hardness have been improved by adjusting the ratio of the cage structure to the ladder structure. In particular, the size of the voids between the network structures formed during coating of a coating composition having a cage structure to ladder structure ratio of 10 wt%:90 wt% to 80 wt%:20 wt% was reduced, significantly reducing the moisture permeability and significantly improving the surface hardness.
[0025] In addition, the initiator contained in the coating composition of the present invention is not particularly limited, and specifically, a photoradical initiator, a photocationic initiator, a thermal radical initiator, or a thermal cationic initiator can be used. In the coating composition of the present invention, the content of the initiator is preferably 0.1 to 10% by weight. Within this range, the excellent moisture resistance and excellent surface hardness of the TAC film can be simultaneously satisfied.
[0026] In addition, the solvent usable in the present invention is not particularly limited as long as it has solubility and does not affect the reaction, and specifically, the organic solvent may be, but is not limited to, polar solvents such as alcohols, ketones, glycols, furans, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, hexane, cyclohexane, cyclohexanone, toluene, xylene, cresol, chloroform, dichlorobenzene, dimethylbenzene, trimethylbenzene, pyridine, methylnaphthalene, nitromethane, acrylonitrile, methylene chloride, octadecylamine, aniline, dimethylsulfoxide, benzyl alcohol, etc. In the present invention, the solvent may be the remaining amount excluding the silsesquioxane oligomer, the initiator, and optional additives.
[0027] The coating composition of the present invention may further contain a silicon-based additive or an acrylic-based additive, if necessary.
[0028] The silicone additives of the coating composition include BYK-300, BYK-301, BYK-302, BYK-331, BYK-335, BYK-306, BYK-330, BYK-341, BYK-344, BYK-307, BYK-333, and BYK-310, and the acrylic additives include BYK-340, BYK-350, BYK-352, BYK-354, BYK-355, BYK-356, BYK-358N, BYK-359, BYK-361N, BYK-380N, BYK-381, BYK-388, BYK-390, BYK-392, and BYK-394. Each of the additives may be added independently in an amount of 0.01 to 5% by weight. When the silicone-based additive is included, the surface slip property and coating flatness of the hard coating layer can be further improved, and the moisture permeability resistance can be further improved. In addition, when an acrylic-based additive is used, the leveling property and moisture permeability resistance of the hard coating layer can be further improved. In addition, the hard coating composition of the present invention can further include known additives that can be added to hard coating compositions, such as an antioxidant and a leveling agent, as necessary.
[0029] The present invention also provides a film obtained by coating the coating composition on a substrate and curing it.
[0030] The coating composition according to the present invention has a coating weight of 4 g / m 2 In particular, the coating composition can be applied to films such as PMMA, PET, PC, PES, PVA, PI, COC, etc., and the effect of improving moisture permeability is most effective when the coating composition is applied to a triacetyl cellulose film.
[0031] FIG. 1 illustrates a coated film 100 according to one embodiment of the present invention.
[0032] The coated film 100 of the present invention has a structure in which a cured layer 102 of the coating composition is bonded on a film layer 101. Specifically, the thickness of the cured layer 102 of the coating composition may be 10 to 60 um. The film may be a film of PMMA, PET, PC, PES, PVA, PI, COC, etc., and in particular, a triacetyl cellulose film. Within the above range, the moisture permeability resistance and surface hardness of the coated film 100 can be further improved.
[0033] The cured layer 102 of the coating composition can be formed by coating the coating composition on the surface of the film layer 101 and then drying or curing it. The coating method can be any known method such as spin coating, bar coating, slit coating, dip coating, natural coating, reverse coating, roll coating, curtain coating, spray coating, immersion method, impregnation method, gravure coating, etc., which can be arbitrarily selected and applied by a person skilled in the art.
[0034] Specifically, the cured layer 102 of the coating composition may further include a silicone-based additive and an acrylic-based additive, in which case the moisture resistance and surface hardness of the coated film 100 may be further improved.
[0035] Figure 2 shows the bonding structure of the coating cross section of the coated triacetyl cellulose film 100 of the present invention. As shown in Figure 2, the film layer 101 and the hardened layer 102 of the coating composition are strongly bonded through hydrogen bonds and / or van der Waals bonds, so that the fully coated triacetyl cellulose film 100 has excellent durability in terms of moisture resistance and surface hardness.
[0036] The coated film 100 according to the present invention significantly improves moisture resistance and surface hardness, which are chronic problems of conventional films, and can be usefully applied to optical films such as protective films for polarizing plates and supports for viewing angle widening films.
[0037] Hereinafter, specific examples will be presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and the scope of the present invention is not limited to the following examples.
[0038] [Catalyst production] To adjust the basicity, a catalyst was prepared by mixing a 25% by weight aqueous solution of tetramethylammonium hydroxide with a 10% aqueous solution of potassium hydroxide.
[0039] [Synthesis Example 1] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 20 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 10:90 was obtained.
[0040] [Synthesis Example 2] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 50 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 30:70 was obtained.
[0041] [Synthesis Example 3] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 90 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a 50:50 ratio of cage-type silsesquioxane and ladder-type silsesquioxane was obtained.
[0042] [Synthesis Example 4] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 220 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 80:20 was obtained.
[0043] [Synthesis Example 5] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 7 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 3:97 was obtained.
[0044] [Synthesis Example 6] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 10 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 5:95 was obtained.
[0045] [Synthesis Example 7] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 260 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 85:15 was obtained.
[0046] [Synthesis Example 8] In a dried flask equipped with a condenser and stirrer, 10 parts by weight of distilled water, 280 parts by weight of acetonitrile (Oi Chemical Industries, Ltd.), and 2 parts by weight of the produced catalyst were added dropwise and stirred at room temperature for 1 hour, after which 20 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., product name KBM-303) was added dropwise and stirred for an additional 6 hours. After the reaction was completed, the catalyst and impurities were extracted by washing twice, and finally a silsesquioxane oligomer having a cage-type silsesquioxane and ladder-type silsesquioxane ratio of 90:10 was obtained.
[0047] [Example 1] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 1 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of silicon-based additive BYK-302, and 1 part by weight of acrylic additive BYK-359 were added to 100 parts by weight of the prepared composition and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure: ladder structure ratio of 10%:90% by weight. The prepared photocurable resin composition was coated on an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then 1 J / cm was applied using UV equipment. 2 The result was obtained by irradiating the sample with UV light.
[0048] [Example 2] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 2 was dissolved in methyl isobutyl ketone at 50 wt % to prepare 100 g of a composition. Then, 1 part by weight of acrylic additive BYK-359 was added to 100 parts by weight of the prepared composition and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure to ladder structure ratio of 30 wt %:70 wt %. The prepared photocurable resin composition was coated on an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then 1 J / cm was applied using UV equipment. 2 The result was obtained by irradiating the sample with UV light.
[0049] [Example 3] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 3 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of silicon-based additive BYK-302, and 1 part by weight of acrylic additive BYK-359 were added to 100 parts by weight of the prepared composition and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure to ladder structure ratio of 50% by weight:50% by weight. The prepared photocurable resin composition was coated on an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then 1 J / cm was applied using UV equipment. 2The result was obtained by irradiating the sample with UV light.
[0050] [Example 4] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 4 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of a silicon-based additive BYK-302, and 1 part by weight of an acrylic-based additive BYK-359 were added to 100 parts by weight of the prepared composition, and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure to ladder structure ratio of 80% by weight:20% by weight. The prepared photocurable resin composition was coated on an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then 1 J / cm was applied using UV equipment. 2 The result was obtained by irradiating the sample with UV light.
[0051] [Example 5] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 2 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of a silicon-based additive BYK-302, and 1 part by weight of an acrylic-based additive BYK-359 were added to 100 parts by weight of the prepared composition, and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure to ladder structure ratio of 30% by weight:70% by weight. The prepared photocurable resin composition was coated on an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then 1 J / cm was applied using UV equipment. 2 The UV was irradiated on the other side and the same process was repeated on both sides to obtain the result.
[0052] [Comparative Example 1] The following experiments were carried out using only the 80 μm triacetyl cellulose film (FUJIFILM) used as the coating substrate in the examples and comparative examples.
[0053] [Comparative Example 2] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 5 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of silicon-based additive BYK-302, and 1 part by weight of acrylic additive BYK-359 were added to 100 parts by weight of the prepared composition and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure to ladder structure ratio of 3% by weight:97% by weight. The prepared photocurable resin composition was coated on an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then 1 J / cm was applied using UV equipment. 2 The result was obtained by irradiating the sample with UV light.
[0054] [Comparative Example 3] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 6 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of a silicon-based additive BYK-302, and 1 part by weight of an acrylic-based additive BYK-359 were added to 100 parts by weight of the prepared composition, and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure / ladder structure ratio of 5% by weight:95% by weight. The prepared photocurable resin composition was applied onto an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then the UV equipment was used to irradiate the film with 1 J / cm 2 The result was obtained by irradiating the sample with UV light.
[0055] [Comparative Example 4] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 7 was dissolved in methyl isobutyl ketone at 50 wt % to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of a silicon-based additive BYK-302, and 1 part by weight of an acrylic-based additive BYK-359 were added to 100 parts by weight of the prepared composition, and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure / ladder structure ratio of 85 wt %:15 wt %. The prepared photocurable resin composition was applied onto an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then the UV equipment was used to irradiate the film with 1 J / cm 2 The result was obtained by irradiating the sample with UV light.
[0056] [Comparative Example 5] 50 g of the silsesquioxane oligomer obtained in Synthesis Example 8 was dissolved in methyl isobutyl ketone at 50% by weight to prepare 100 g of a composition. Then, 5 parts by weight of chloroacetophenone, 1 part by weight of a silicon-based additive BYK-302, and 1 part by weight of an acrylic-based additive BYK-359 were added to 100 parts by weight of the prepared composition, and stirred for 10 minutes to prepare a photocurable resin composition with a cage structure / ladder structure ratio of 90% by weight:10% by weight.
[0057] The prepared photocurable resin composition was applied onto an 80 μm triacetyl cellulose film (FUJIFILM), the solvent was evaporated in a drying oven at 85°C, and then the UV equipment was used to irradiate the film with 1 J / cm 2 The result was obtained by irradiating the sample with UV light.
[0058] [experiment] The pencil hardness, adhesion, transmittance, haze, and moisture transmittance were measured before and after coating for the results obtained in Example 1, Example 2, Example 3, Example 4, Example 5, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5, and the results are shown in Table 1 below. - Pencil hardness: Evaluated with a load of 500g based on JIS5600-5-4. Mitsubishi pencils were used, and tests were conducted five times for each pencil hardness. If two or more scratches occurred, the product was judged to be defective. The results were expressed as the measured hardness and the number of times no scratches occurred divided by the number of tests conducted. -Adhesion evaluation: According to JIS K5600-5-6, 100 scratches were made in a grid pattern at 1 mm intervals with a cutter blade, adhesive tape was applied on top of the scratches, and then the tape was peeled off at a 90 degree angle to check with the naked eye whether the surface of the coating layer was adhered to the adhesive tape. The number of scratches that were adhered out of 100 scratches was indicated. (For example, it is expressed as the number of particles attached / 100, so if there are 100 particles attached, it is expressed as 100 / 100.) -Transmittance and haze: Based on ISO14782, COH-400 (Nippon The measurements were made five times for each sample, and the average values were reported. -Moisture permeability: Measured using MOCON equipment at constant temperature and humidity of 37.8°C and 100% RH (Relative Humidity). [Table 1]
[0059] As shown in Table 1, Examples 2, 3, and 5 of the present invention exhibited significantly better physical properties than Example 1, Example 4, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5. In particular, it can be seen that Example 2 and its double-sided coating Example 5 have better moisture permeability and pencil hardness of the TAC film. [Industrial Applicability]
[0060] It can be used for optical films such as protective films for polarizing plates and supports for viewing angle expanding films.
Claims
1. A coating composition comprising a silsesquioxane oligomer in which the weight ratio of a cage-type silsesquioxane resin to a ladder-type silsesquioxane resin is from 10% by weight:90% by weight to 80% by weight:20% by weight.
2. The coating composition according to claim 1, wherein the silsesquioxane oligomer is a ladder-type silsesquioxane resin represented by Chemical Formula 1 and a cage-type silsesquioxane resin represented by Chemical Formula 2 bonded to the ladder-type silsesquioxane resin represented by Chemical Formula 1. 【Chemistry 1】 In the above Chemical Formula 1, R 1 , R 2 , R 3 , R 4 each independently represents a methyl group, which may be substituted or unsubstituted; a phenyl group; an amino group; a (meth)acrylic group; a vinyl group; an epoxy group; a thiol group; or an ultraviolet absorber, and n represents an integer of 1 to 100, R 5 , R 6 , R 7 , R 8 are each independently hydrogen; a C1 to C10 alkyl group which may be substituted or unsubstituted; or a linking group represented by the following chemical formula 2, 5 , R 6 , R 7 , R 8 At least one of the following formula 2 is linked to 【Chemistry 2】 In the above Chemical Formula 2, R is independently a methyl group, a phenyl group, an amino group, a (meth)acrylic group, a vinyl group, an epoxy group, a thiol group, or an ultraviolet absorber, each of which may be substituted or unsubstituted; R 0 Each independently represents hydrogen or a C substituted or unsubstituted by a substituent. 1 ~C 10 is an alkyl group of the formula n is an integer from 3 to 6; In Formula 1 or 2, the substituents are each independently deuterium, a halogen, an amine group, an epoxy group, a (meth)acrylic group, a thiol group, an isocyanate group, a nitrile group, a nitro group, or a phenyl group.
3. The coating composition of claim 1 , further comprising at least one of a light- or heat-initiated cationic initiator, a radical initiator, or a solvent.
4. A film obtained by coating the coating composition according to any one of claims 1 to 3 on a substrate and curing it.
5. The moisture permeability of the substrate is 4 g / m 2 5. The film of claim 4, wherein the film has a viscosity of 1.0 s or more.
6. The film of claim 4 , wherein the substrate is triacetyl cellulose.
7. The film is 100 g / m 2 7. The film of claim 6, having a moisture permeability of less than or equal to 1.0 MPa.